Hungarian Monitoring, 25 May 1989 . [Magyar rádiófigyelő], 1989. május 25 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Correspondence from Beijing - Soviet opinion polls indicate that half of the Soviet population wants openness and strengthening of freedom of speech - Estonia still plans to form economic zone independent of USSR - NATO general secretary rejects idea that NATO and Warsaw Pact be dissolved at the same time - France cancels poorest developing countries' debts - Arab summit Domestic Affairs: - Németh-Vranitzky talks in Vienna on the dam affair - Németh receives Dutch defense minister - In practice it is certain that Vienna and Budapest will win right to hold 1995 World Exposition - Alliance of Free Democrats (SZDSZ) expert and general secretary of Austrian Greens' opinion on the World Exposition - Péter Medgyessy holds talks in Switzerland - Cardinal Paskai's Transcarpathian visit finishes with press conference in Uzhgorod Economy: - Government and Chamber of Commerce hold joint talks to discuss economic plan package - Pricing Office president states it would be good to successfully halt acceleration of inflation - Pál Iványi says it is regrettable that the IMF judges the country's economic situation exclusively according to how the market functions Külpolitika: - Pekingi tudósítások - Szovjet közvélemény kutatási adatok szerint a szovjet polgárok közel fele a nyíltság, a szólásszabadság megerősítését kívánja - Észtországban továbbra is a SZU-tól önálló gazdasági környezet kialakítását tervezik - A NATO-főtitkár visszautasítja, hogy a NATO-t és a VSZ-t egyszerre oszlassák fel - Franciaország elengedi a legszegényebb fejlődő országok tartozásait - Az arab csúcsértekezletről Belpolitika: - Németh-Vranitzky megbeszélés Bécsben vízlépcső ügyben - Németh fogadta a holland védelmi minisztert - Gyakorlatilag biztosra vehető, hogy Bécs és Budapest megkapja a az 1995-ös világkiállítás rendezési jogát - Az SZDSZ szakértőjének - És az osztrák zöldek főtitkárának véleménye a világkiállításról - Svájcban tárgyal Medgyessy Péter - Paskai bíboros kárpátaljai látogatása befejeztével sajtóértekezletet tartott Ungváron Gazdaság: - A kormány és a Gazdasági Kamara közös ülésen vitatja meg a gazdasági csomagtervet - Az Árhivatal elnöke kijelentette, már az is jó, ha sikerül megállítani az infláció gyorsulását - Iványi Pál sajnálatosnak nevezte, hogy a Nemzetközi Valutaalap az ország gazdasági helyzetét kizárólag aszerint ítéli meg, hogy mennyire működik a piac